2021
DOI: 10.2147/ijwh.s282251
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Preterm Delivery in Singleton Pregnancy in a Tertiary Care Hospital in South India: A Case Control Study

Abstract: Background Preterm delivery is a major obstetric complication and a leading cause of neonatal mortality and morbidity. It is also associated with significant costs in terms of psychological and financial hardship, to the families. Objective The primary objective of this study was to determine the risk factors associated with all preterm deliveries in singleton pregnancy in a tertiary care hospital and the secondary objective was to determine the fetal outcomes among wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
4
14
0
Order By: Relevance
“…Factors associated with increased risk of preterm birth at India sites included severe antepartum haemorrhage, maternal hypertensive disorders, fetal malpresentation, and moderate/severe anaemia recorded anytime during pregnancy [ 10 ]. PROM was evident in 29.96% of our study participants; this finding accords with another Indian study from Kerela [ 23 ]. Anaemia, IUGR, and preeclampsia/eclampsia were the most common adverse pregnancy conditions prevalent in the present study after PROM.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Factors associated with increased risk of preterm birth at India sites included severe antepartum haemorrhage, maternal hypertensive disorders, fetal malpresentation, and moderate/severe anaemia recorded anytime during pregnancy [ 10 ]. PROM was evident in 29.96% of our study participants; this finding accords with another Indian study from Kerela [ 23 ]. Anaemia, IUGR, and preeclampsia/eclampsia were the most common adverse pregnancy conditions prevalent in the present study after PROM.…”
Section: Discussionsupporting
confidence: 92%
“…The average birth weight of preterm babies tends to be significantly lower as compared to the term babies. The mean birth weight of preterm neonates in our study was 2205.76 ± 701.33 grams, which is similar to another Indian study in which the average preterm birth weight was 2.1 ± 0.6 kg [ 23 ]. The effect of preeclampsia, IUGR, and associated anaemia on the birth weight of premature babies has to be taken into consideration.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study finding was in line with the study conducted in Kambala International University Teaching Hospital in Uganda 7.5% [12], Brazil 3.1% [3], Egypt 5.3% [6], and Nigeria 3.3% [7]. This finding was also higher than the study conducted in India 2.01% [13] and south Kerala India 0.8% 3 Infectious Diseases in Obstetrics and Gynecology [4]. The discrepancy might be due to differences in accessibility and service quality in the study area.…”
Section: Discussionsupporting
confidence: 90%
“…Women with GH have a significantly increased risk of preterm birth compared with healthy pregnant women [ 11 ]. In addition, special attention and intervention for women with HPB are also beneficial [ 12 , 13 ]. Studies have found that GH and HPB have been identified to be risk factors for preterm birth [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%